Landscape, natural beauty, and the arts - Kemal, Salim (Cambridge studies in philosophy and the arts, 1993)
Landscape, Natural Beauty and the Arts offers probing studies of the complex structure of aesthetic responses to nature. Each chapter refines and expands the terms of discussion, and together they enrich the debate with insights from art history, literary criticism, geography and philosophy. To explore the interrelation between our conceptions of nature, beauty and art, the contributors consider the social construction of nature, the determination of our appreciation by artistic media, and the duality of nature's determining in gardening. Showing that natural beauty is impregnated with concepts derived from the arts and from particular accounts of nature, the volume occasions questions of the distinction and relation between art and nature generally, and culminates in a set of philosophical studies of the role of scientific understanding, engagement and emotion in the aesthetic appreciation of nature